On the taxonomic status of the genus Hypeugoa Leech with description of a new species of Miltochrista Hübner from Thailand (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2021)
The genus Hypeugoa Leech, 1899 is synonymized with the nominate subgenus of the genus Stigmatophora Staudinger, 1881: Stigmatophora = Hypeugoa, syn. nov., and a new combination for the type species is established: Stigmatophora flavogrisea (Leech, 1899), comb. nov. Hypeugoa flavogrisea orientalis Daniel, 1951 is upgraded to species level and also assigned with Stigmatophora: Stigmatophora orientalis (Daniel, 1951), stat. & comb. nov. Hypeugoa radaricola Černý, 2009 is transferred to the genus Miltochrista Hübner, [1819]: Miltochrista radaricola (Černý, 2009), comb. nov. A new species similar to M. radaricola, Miltochrista eugoana sp. nov. is described from North Thailand. The original citation of the holotype label of M. radaricola is corrected. Adults together with male and female genitalia of the new and the similar species are illustrated.